2020
DOI: 10.2147/opth.s223530
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anesthesia for Intravitreal Injection: A Systematic Review</p>

Abstract: Background: The intravitreal injection has become one of the most commonly performed procedures in ophthalmology; however, there is no standardized approach to anesthesia during the procedure. The goal of this systematic review is to review approaches to anesthesia for intravitreal injection and look at comparative efficacy between these different anesthetics. Methods: A systematic review of literature was performed in the MEDLINE, PubMed, Cochrane Library, and Clinicaltrials.gov databases using the key words … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…These pain scores are in a similar range of pain scores reported from other prospective studies evaluating anesthetic agents during IVTs. 10 While this study was not powered to detect differences in pain scores between different cooling regimens, we did not observe any statistically significant difference of pain scores at the time of injection in pairwise comparisons between the three groups. It should also be noted that the sensitivity of this pain scale to detect small changes in pain perception is unknown.…”
Section: Discussionmentioning
confidence: 65%
“…These pain scores are in a similar range of pain scores reported from other prospective studies evaluating anesthetic agents during IVTs. 10 While this study was not powered to detect differences in pain scores between different cooling regimens, we did not observe any statistically significant difference of pain scores at the time of injection in pairwise comparisons between the three groups. It should also be noted that the sensitivity of this pain scale to detect small changes in pain perception is unknown.…”
Section: Discussionmentioning
confidence: 65%
“…A recent systematic review found no gold standard for anesthesia with respect to patient comfort during the intravitreal injection procedure [ 101 ]. A second systematic review of 847 patients in 8 studies described pain associated with intravitreal injections as “mild” (visual analog scale rating 5–44 mm).…”
Section: Resultsmentioning
confidence: 99%
“…18 A survey of Canadian retina specialists showed that at least a quarter of them routinely used subconjunctival anaesthetics and up to half of them infrequently used the same. 19,20 Complications reported in the literature of intravitreal injections include raised intraocular pressure, uveitis and endophthalmitis. No patient in our study reported these complications.…”
Section: Discussionmentioning
confidence: 99%